The influence of caregivers on the self-help skills of preschoolers - Lagos, Marita P.; Trio, Consuelo Q. (Quezon City College of Home Economics, University of the Philippines Diliman, 2010)
ABSTRACT This study compared the independence level of preschoolers who grew up being co-reared by caregivers and those who did not in performing the following self-help skills: dressing, feeding, personal hygiene, play time, and getting around. The strategies that caregivers use to teach and motivate the children to perform the self-help tasks were also examined. A sample of twenty four-year old children, ten of whom grew up with a caregiver and the other ten without, were purposely selected for the study. The respective caregivers of the children also participated as respondents. Unobtrusive observation, using the Self-help Skills Rubric as a tool, was utilized to measure the preschoolers? independence level on the five dimensions of self-help skills. On the other hand, in-depth interview was employed in order to gather information about the strategies that caregivers use to teach and motivate their charges to learn the self-help tasks. The Kolmogorov-Smirnov Two-tailed Test was used to compare the independence levels of the two groups of preschoolers in fulfilling self-help tasks. Content analysis was employed to analyze the teaching and motivational strategies of caregivers. Results show that children without caregivers are more independent that the other group in performing self-help tasks, specifically, dressing and feeding. Modeling emerged to be the most common method used by caregivers in teaching self-help skills to their charges, followed by guided learning and verbal instruction. On the other hand, the most common motivational strategy used by caregivers is conditioning, such as giving affection and cuddling. Positive reinforcement, specifically providing material rewards and privileges, is also used. Recommendations for researchers, educators, and family workers are provided at the end of the paper.
Thesis (B.S. Home Economics)--University of the Philippines Diliman.
Keywords: Caregivers